2017
DOI: 10.1016/j.renene.2016.08.041
|View full text |Cite
|
Sign up to set email alerts
|

New materials for adsorption heat transformation and storage

Abstract: Great current progress in the materials science offers an enormous choice of novel adsorbents which may be promising for transformation and storage of low temperature heat, e.g. from renewable heat sources. This paper gives an overview of recent trends and achievements in this field. We consider possible optimization of zeolites by dealumination, further development on aluminophosphates, composites salt in porous host matrice and metal-organic frameworks which are currently receiving the largest share of scien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
77
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 138 publications
(79 citation statements)
references
References 81 publications
1
77
0
1
Order By: Relevance
“…The results showed that the microporoush ydrophilic Al-dicarboxylate MIL-160(Al) exhibited one of the best performances. [5] For example, silica gel can be regenerated at very low temperature (< 45-50 8C), but its low water-sorption capacity resultsi np oor loading lift (0.03-0.10 gg À1 )w ithin at ypical adsorption heatp ump (AHP) cycle. This led to the production of MIL-160(Al) on a4 00 gs cale, before the material was shaped into pelletst hrough aw et-granulation method.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The results showed that the microporoush ydrophilic Al-dicarboxylate MIL-160(Al) exhibited one of the best performances. [5] For example, silica gel can be regenerated at very low temperature (< 45-50 8C), but its low water-sorption capacity resultsi np oor loading lift (0.03-0.10 gg À1 )w ithin at ypical adsorption heatp ump (AHP) cycle. This led to the production of MIL-160(Al) on a4 00 gs cale, before the material was shaped into pelletst hrough aw et-granulation method.…”
Section: Introductionmentioning
confidence: 99%
“…10 times less) than those that are required for the same application using sensible heat storage. [5,16] In this study,w ef irst considered as eries of water-stable, porousM OFs based on high-valencem etal cations (Al 3 + ,F e 3 + , Cr 3 + ,T i 4 + ,Z r 4 + )a nd polycarboxylate aromatic linkers for use in heat reallocation by evaluating their water cycling loading lifts (the amount of water exchanged between the adsorption and desorption steps of the entire cycle in fixed conditions of T and p)a nd their energy-storage capacities (the amount of energy stored by materialp er unit of mass). [2][3][4] In addition to as uitable stabilitya fter numerous workingc ycles, the major requirements for energy-storage materials are ah igh adsorption uptake at relatively low relative pressure and regeneration under mild temperature conditions (desorption within the 80-100 8Cr ange).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A coating has several advantages compared to the loose powder because the interface contact is improved and the quantity of porous material needed is optimized as well as the mechanical and thermal stability of the adsorber module [27,28]. Several different solutions have been proposed, like the direct synthesis of the adsorbing material on the heat exchanger surfaces [29,30] or the use of binders and ligands to make coatings [23,31] or the use of metallic or polymeric fibres or foams [32][33][34][35]. Each of these solutions, however, has many restrictions due to the scale up to an industrial level maintaining competitive production costs.…”
mentioning
confidence: 99%